The dynamics of the F+H-2 reaction - Manolopoulos, D (1997)
This research article reviews the recent progress that has been made in understanding the dynamics of the prototypical exothermic exchange reaction F + H2 → HF + H. The emphasis of the review is on the role of quantum-mechanical reactive scattering resonances in the reaction and their implications for various experimental measurements. The article ends by summarising some of the remaining questions about the dynamics of the reaction that require further experimental and theoretical work.